Microalgae Diversity as a Bioindicator of Water Quality in Batujai Dam, Central Lombok - Hairunnadawiah Hairunnadawiah; Khairuddin Khairuddin; Lalu Zulkifli (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Batujai Dam is one of the largest dams in Central Lombok with an area of 890 ha of inundated water. The water from the Batujai Dam is used for irrigation of agricultural land, flood control, freshwater fisheries and the development of micro-hydro power plants. Batujai Dam is also a reservoir for several rivers in Central Lombok, namely:ÃÂ the Leneng River, the Sade River and the Dodokan River. This function makes the Batujai Dam a place for the accumulation of various forms of pollutants carried by the inlet rivers. Microalgae is one of the ecological parameters that can function as a bioindicator of water quality. The purpose of this study was to determine the water quality in the Batujai Dam in terms of the microalgae diversity index and the measurement of environmental factors. Determination of sampling point and sampling time using purposive sampling method. Measurement of water quality is carried out by determining the diversity index and measuring environmental factors such as pH, temperature, DO, BOD, phosphate and nitrate. Microalgae data for determining the diversity index was analyzed using the Microsoft Excel 2010 program. The results showed that the identified microalgae consisted of 5 classes, 16 orders and 40 species. The overall diversity index of microalgae in the Batujai dam is 1.712 with a DO value of 5.09 and a BOD of 4.0175. Based on these data, it can be concluded that the water quality in the Batujai Dam is in an unhealthy condition (lightly polluted). The allotment for the use of water from the Batujai Dam is suitable for freshwater fish farming, livestock and agricultural irrigation, and it is not recommended for drinking water sources and water recreation infrastructure/facilities.